2022
DOI: 10.1186/s12888-022-04056-1
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness and coping skill mediate the association between child maltreatment and depression for rural males and females

Abstract: Background Child maltreatment is a prevalent and notable problem in rural China, and the prevalence and severity of depression in rural areas are higher than the national norm. Several studies have found that loneliness and coping skills respectively mediated the relationship between child maltreatment and depression. However, few studies have examined the roles of loneliness and coping skills in child maltreatment and depression based on gender differences. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…It is well-established that the various forms of child abuse perpetrated by parents or other caregivers harm the overall development of children and adolescents [ 34 36 ]. Likewise, associations are found with poor cognitive abilities or performance in childhood and even into adulthood, especially with specific types of abuse that will lead to the loss of opportunities and limited personal development [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-established that the various forms of child abuse perpetrated by parents or other caregivers harm the overall development of children and adolescents [ 34 36 ]. Likewise, associations are found with poor cognitive abilities or performance in childhood and even into adulthood, especially with specific types of abuse that will lead to the loss of opportunities and limited personal development [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…The stress sensitivity theory posits that individuals who have experienced childhood trauma have lower stress thresholds and are more prone to experiencing adverse mental health outcomes, such as loneliness and depressive symptoms, compared to those who have not experienced childhood trauma (8). Studies (9,10) have indicated that exposure to negative events in childhood, such as abuse and neglect, can elevate the risk of loneliness and depressive symptoms. Hence, it is plausible that nurses who have experienced more childhood trauma may be predisposed to developing loneliness and depressive symptoms.…”
Section: Potential Mediation Mechanism Between Childhood Trauma Lonel...mentioning
confidence: 99%
“…Many mediators have been used to explain the development of depressive symptoms following childhood maltreatment experiences. Examples include envy ( 6 ), loneliness and lack of coping skills ( 7 ), scarcer social support ( 8 ), and lower parent-child relationship quality ( 9 ). Recent research has focused more on emotion dysregulation, which refers to an individual’s inability to control or regulate their emotional responses to a stimulus ( 10 13 ).…”
Section: Introductionmentioning
confidence: 99%